2010
DOI: 10.2298/avb1004401s
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical markers of bone metabolism in dairy cows with milk fever

Abstract: Bone metabolism was investigated in 8 healthy and 12 dairy cows suffering from milk fever (MF) in intensive dairy production. Blood samples were taken within 48 hours after calving in healthy cows and before treatment in cows with MF. Bone and mineral metabolism were evaluated by measuring blood serum bone resorption biomarker Cterminal telopeptide of type I collagen (CTx) and bone formation biomarker bone-specific alkaline phosphatase (bALP) beside the classical panel: total calcium (Ca), inorganic phosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
3
2
0
Order By: Relevance
“…The ALP was significantly higher in group A than in the other groups. These results were in accordance with (Stari and Zadnik, 2010). The serum glucose level was significantly lower in group A than in other groups.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The ALP was significantly higher in group A than in the other groups. These results were in accordance with (Stari and Zadnik, 2010). The serum glucose level was significantly lower in group A than in other groups.…”
Section: Discussionsupporting
confidence: 90%
“…This is may be attributed to the restricted feeding or to the effect of the hypocalcaemia. Oxalates are reported to have an irreversible effect on energy metabolism and plasma glucose level (Knight and Walter, 2003;Stari and Zadnik, 2010). The serum calcitonin level was significantly low in group A than in other groups, this may be attributed to the restricted food intake especially with low calcium level in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to fatty liver changes. The results come in agreement with [40,41].Stari and Zadnik [41]revealed that the recumbency of milk fever cows could have a negative effect on hepatic tissue and consequently result in a rise of activity of liver enzymes.…”
Section: Discussionsupporting
confidence: 89%
“…Similar conclusions were made by other studies using CTx or other bone resorption markers (11,37,41,42). In a study where biochemical bone markers between healthy and cows with milk fever were compared, higher values of bALP and lower values of CTx were observed in milk fever cows, however, the differences were not statistically significant (33).…”
Section: Discussionsupporting
confidence: 82%
“…Prevalence of hypocalcaemia and milk fever was within the expected range for fourth or higher lactation cows fed a diet with DCAD of more than 200 mEq/kg DM in the close-up dry period (1). Mg was highest after calving (32,33) in all except in the vitamin D group, which showed a decline in Mg concentrations throughout the study. The vitamin D group had the lowest values of Mg and the highest for tCa after calving, which is in-line with the inverse association between Ca and Mg reported by Larsen et al (34).…”
Section: Discussionmentioning
confidence: 56%